Juvenile justice: punitive perspectives on children, sex offences and the age of criminal responsibility - Taylor, Rhiannon (2020)
There are social and legislative drives to investigate factors that may diminish criminal responsibility within juvenile sexual offenders, and whether they are publicly perceived to hold moral capacity on sexual deviancy. The current study aimed to measure attitudes towards the criminal responsibility of juvenile sexual offenders; in relation to perpetrator age, intellectual disability and type of sexual coercion committed. This study also assessed associations between perceived criminal responsibility, attitudes towards treatment of sexual offenders, and understanding of UK age legislation. A sample of 206 UK adults found juveniles were more likely to be perceived of diminished criminal responsibility when involved in a sexual relationship with a peer of the same developmental age; diagnosed with an intellectual disability; and committing a non-contact offence. Overall attitudes towards the treatment of juvenile sexual offenders were positive, with significant associations between perceptions of treatment and perceptions of criminal responsibility. Understanding of UK age legislation demonstrated that participants had an overall poor understanding of the age of criminal responsibility – presenting no significant associations. Limitations and implications for evidence-based sex offender policies are discussed.